Different interventions for OHVIRA/Herlyn-Werner-Wunderlich syndrome based on age and symptoms: a single-institution cohort study - Tomoko Oishi; Kota Konishi; Mamiko Okamoto; Chiharu Mizoguchi; Mitsutake Yano; Yasushi Kawano; Eiji Kobayashi (BMC Women's Health)
Abstract Background This study aimed to describe the clinical characteristics of patients with obstructed hemivagina and ipsilateral renal anomaly (OHVIRA)/Herlyn-Werner-Wunderlich (HWW) syndrome and to evaluate the efficacy of minimally invasive management strategies. Methods This cohort study involved a retrospective review of the medical records of patients diagnosed with OHVIRA/ HWW syndrome. Data on chief complaints, diagnostic findings, associated complications, anatomical variations, and therapeutic interventions were extracted. Results A total of nine cases were eventually included. The mean age of symptom onset was 23.1 years, whereas the mean age at diagnosis was 20.3 years. Six patients (67%) were diagnosed with OHVIRA syndrome, and an equal proportion (67%) had left-sided abnormalities. Therapeutic interventions were performed in five cases (56%). Statistically, diagnosis after menarche and severe dysmenorrhea was positively correlated with therapeutic interventions (p = 0.048 and p = 0.040, respectively). In one case, symptoms appeared after amenorrhea due to pregnancy, leading to a first-time diagnosis of HWW syndrome in the patient. Management strategies included traditional transvaginal surgery in three patients, vaginoscopic surgery in one patient, and hormone therapy without surgical intervention in another. Conclusions Early diagnosis before menarche reduces the risk of therapeutic intervention, while severe dysmenorrhea is a risk factor for therapeutic interventions. Amenorrhea due to pregnancy can result in the re-closure of a pre-existing communicating tract. Minimally invasive management approaches, such as hormone therapy without surgery or vaginoscopic incision, can be effective.